Dosa Bani Israel pada QS Al Maidah Ayat 72-78 dalam Perspektif Self Awareness Goleman - Nisa Shalihah; Waharjani Waharjani; Djamaluddin Perawiranegoro (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
QS Al Ma'idah verses 72-78 explains the history of Israel clan who had bad morals towards Allah SWT and the Messenger, so that they became a people who were cursed in the Qur'an and caused hatred and sentiment to Jewish people. This is a challenge for the realization of religious moderation, especially for Muslims, to act toward Jews who are not hostile to Islam. Goleman in his theory of emotion competencies provides a perspective on ideal human behavior to analyze the behavior of Israel clan as humans who have emotions and awareness. The purpose of this research is to analyze the despicable behavior of the Israel in Goleman's self-awareness perspective. The methods of this research is literature research (library research). Researchers use content-analysis techniques to draw a valid conclusion based on the object of study. The results of the study concluded that Israel clan did not have good self awareness at that time. This is demonstrated by historical facts from the Qur'an and other books which show the behavior of Israel.